EFFECT OF BEHAVIOURAL REHEARSAL TECHNIQUE ON TEST ANXIETY AMONG SECONDARY SCHOOL STUDENTS IN AWKA EDUCATION ZONE OF ANAMBRA STATE, NIGERIA (Journal of Guidance and Counselling Studies, 2022)
This study determined the effect of behavioural rehearsal technique on test anxiety among secondary school students in Awka Education Zone of Anambra State, Nigeria. Specifically, the study tends to ascertain the effect of behavioural rehearsal on test anxiety of secondary school students when compared to those in the control group using their pre- test and post- test mean score and to determine the effectiveness of behavioural rehearsal technique on test anxiety of male and female secondary school students using their pre-test and post- test mean score. The study is a quasi- experimental research. The specific design adopted is non- randomized pre-test and post-test control group design. This study consists of two groups of participants from three co-educational schools sampled. The Population of the study comprises of 580 SS 1 and SS2 students in the 62 government owned secondary schools in Awka Education Zone. The instrument used for data collection was an adopted Speideger test anxiety inventory. Mean was used in answering the research questions, and analysis of covariance (ANCOVA) was used in testing the hypotheses. The study found among others that behavioural rehearsal technique had significant positive effect on students’ test anxiety irrespective of their gender. While the study recommends that Guidance Counsellors in secondary schools should adopt behavioural rehearsal technique on test anxiety.
Keywords: Effect; Test anxiety; Behavioural rehearsal; Secondary school; Students